2021
DOI: 10.3390/metabo11120819
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sebum Lipidomics to Biomarkers Discovery in Neurodegenerative Diseases

Abstract: Lipidomics is strategic in the discovery of biomarkers of neurodegenerative diseases (NDDs). The skin surface lipidome bears the potential to provide biomarker candidates in the detection of pathological processes occurring in distal organs. We investigated the sebum composition to search diagnostic and, possibly, prognostic, biomarkers of Alzheimer’s disease (AD) and Parkinson’s disease (PD). The observational study included 64 subjects: 20 characterized as “probable AD with documented decline”, 20 as “clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…More recently, as changes in the circulating lipids seem to mirror the dysregulation of their profile in the brain, blood has become a viable alternative to invasive CSF sampling [ 299 , 300 , 301 ]. At the same time, the emergence of cutting-edge techniques, such as peripheral lipidomics, triple quadrupole mass spectrometry, and isobaric tagging methods, have allowed the establishment of lipid signatures potentially associated with AD, even at the prodromal and preclinical stages [ 302 , 303 , 304 ]. Lipid peroxidation, caused by oxidative stress, is one of the most-studied markers of disease, and various molecules have been proposed as potential circulating biomarkers (See Section 3.5 Oxidative Stress ) [ 166 , 167 , 182 , 305 , 306 , 307 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, as changes in the circulating lipids seem to mirror the dysregulation of their profile in the brain, blood has become a viable alternative to invasive CSF sampling [ 299 , 300 , 301 ]. At the same time, the emergence of cutting-edge techniques, such as peripheral lipidomics, triple quadrupole mass spectrometry, and isobaric tagging methods, have allowed the establishment of lipid signatures potentially associated with AD, even at the prodromal and preclinical stages [ 302 , 303 , 304 ]. Lipid peroxidation, caused by oxidative stress, is one of the most-studied markers of disease, and various molecules have been proposed as potential circulating biomarkers (See Section 3.5 Oxidative Stress ) [ 166 , 167 , 182 , 305 , 306 , 307 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yet, some particularly advanced and cutting-edge techniques, such as peripheral lipidomics, triple quadrupole mass spectrometry, and isobaric tagging methods, are particularly burdensome for clinical routine analysis, and here were described for completeness, whereas others are very rarely applied [ 302 , 303 , 304 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Our observation is in line with previous studies that compared medicated and drug-naïve patients with PD, demonstrating that PD medication does not influence production of the compounds responsible for the PD smell. 10,21 Studies show that compounds in the sebum of patients with PD are different from that of non-PD subjects, 10,21,23,24 and the dogs may have taken this advantage to distinguish them.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, epidermal ceramides and sebum lipids have been examined as potential biomarkers of neurodegenerative disease [66 ▪ ,67], and a recent study on the sebum metabolome suggested lipid dysregulation in Parkinson's disease [68 ▪▪ ]. Interestingly, sphingoid base profiles in infant skin can predict the development of atopic dermatitis [69 ▪ ].…”
Section: Skin Lipids Relate To Systemic Health and Diseasementioning
confidence: 99%